Desain Alat Elektrokoagulasi Portabel untuk Penurunan Total Organic Carbon (TOC) pada Limbah Cair Bengkel Kendaraan Otomotif - Pratama, Doni; Retnawaty, Sri Fitria; Fitri, Yulia; Rizky, Mende Karina; Doni Pratama (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
The treatment of wastewater from automotive workshops presents a significant environmental challenge due to the high levels of organic materials, including Total Organic Carbon (TOC). One innovative and efficient solution is the use of electrocoagulation methods. This study aims to design a portable electrocoagulation device and determine an efficient time for reducing TOC levels. In this research, aluminum electrodes are used to induce electrochemical reactions, generating metal ions that can adsorb and precipitate contaminants in workshop wastewater. Experiments were conducted with different electrocoagulation process durations, specifically 3 hours and 5 hours, to measure TOC reduction efficiency. Laboratory test results indicate that electrocoagulation for 3 hours reduced TOC levels by 55.7%, while the 5-hour process achieved an efficiency of 86.4%. This process effectively meets the standard quality threshold for TOC, which is 110 ppm. The advantages of electrocoagulation lie in its high efficiency, lower operational costs, and the absence of the need for additional chemicals, making it a promising solution for wastewater treatment in workshops. This research contributes through an innovative design that can be applied on a small scale, particularly for automotive workshops that need an effective and economical wastewater treatment technology. Keywords: Electrocoagulation, Efficiency, Workshop Wastewater Treatment, Total Organic Carbon (TOC